The effect of inactin on kidney mitochondrial function and production of reactive oxygen species - Palm, Fredrik; Schiffer, Tomas (Uppsala University, 2018)
Inactin is an anesthetic agent commonly used in rat studies, but is also shown to exert physiological effects such as reducing renal blood flow, glomerular filtration rate and depressing tubular transport capacity. It is unknown whether inactin also effects isolated kidney mitochondria which may be important when studying related topics in anaesthetized animals. The aim of this study was to evaluate whether inactin exerts effects on mitochondrial function and production of reactive oxygen species. Kidney mitochondrial function and reactive oxygen production after acutely (5 min) or longer (1.5 hour) anesthetizing rats with inactin was determined by using high-resolution respirometry.

Inaktin är ett bedövningsmedel som ofta används i råttstudier. Det har okså visat sig ha fysiologiska effekter som att minska blodflödet i njurarna, glomerulär filtrationshastighet. Det är okänt om inaktin också påverkar isolerade njurmitokondrier som kan vara viktigt när man studerar relaterade ämnen i bedövade djur. Syftet med denna studie var att utvärdera om inaktin har effekter på mitokondriell funktion och produktion av reaktiva syrearter. Njurmitokondriell funktion och reaktiv syreproduktion efter akut (5 min) eller längre (1,5 timmars) hos inaktinanestetiserande råttor bestämdes genom användning av respirometri med hög upplösning.
Effekterna av inaktin på mitokondriell funktion och produktion av fria syreradikaler
Keywords: Medical and Health Sciences; Medicin och hälsovetenskap